Preparation of Hierarchical Porous ZIF-67 and Its Application in Zinc Battery Separator - Tian Zhao; Jiangrong Yu; Pengcheng Xiao; Saiqun Nie; Shilin Peng; Jiayao Chen; Fuli Luo; Christoph Janiak; Yi Chen (Chemistry)
This study successfully prepared a hierarchically porous ZIF-67 (H-ZIF-67) by incorporating the polyvinylpyrrolidone (PVP) at room temperature. Compared to standard control ZIF-67 (C-ZIF-67) with a yield of 81% and a BET specific surface area of 1228 m2·g−1, the H-ZIF-67 not only exhibited improved crystallinity and pore structure but also achieved a yield of up to 93% and a BET specific surface area of 1457 m2·g−1. Due to its hierarchically porous structure, H-ZIF-67 demonstrated excellent adsorption capacity and efficiency for methylene orange (MO). Additionally, the composite separator created by combining H-ZIF-67 with nanocellulose (CNF) exhibited remarkable uniformity and dispersion in zinc batteries. In comparison to a conventional CNF separator, the porous structure and high specific surface area of H-ZIF-67 significantly enhanced its electrolyte wettability and Zn2+ transport rates. Its abundant Lewis acid sites effectively promoted the uniform deposition of Zn2+, thereby suppressing the formation of zinc dendrites and improving the cycling and safety performance of zinc-ion batteries. Experimental results indicate that the ion conductivity of the membrane was 4.31 mS·cm−1, the electrolyte absorption rate was 316%, and it could cycle stable for over 4000 h at a current density of 1 mA·cm−2 with a discharge capacity of 1 mAh·cm−2. This achievement will open up new avenues for the preparation and application of ZIF-67 composite separators in aqueous zinc-ion batteries.